Smallholder Tobacco Growing in Indonesia : Costs and Profitability Compared with Other Agricultural Enterprises - Keyser, John C.; Ratna Juita, Nila (World Bank, Washington, DC, 2013)
This supply-side study compares the financial costs and returns for smallholder tobacco farming with a selected range of smallholder crops that either complement tobacco or offer long-term diversification potential. It is a first step to understanding how tobacco farmers might be affected if the demand for tobacco fell in Indonesia, and to what extent farmers might be able to adjust by shifting to other crops, and the implications this might have for their incomes. The analysis is based on a set of 24 original per hectare crop budgets estimated specially for this study to reflect the actual costs and returns for tobacco and other farm enterprises in upland and lowland tobacco growing regions of Central Java to the best extent possible. These original budgets cover eight distinct crop enterprises including Virginia-kretek tobacco and seven other crops that either complement tobacco or offer diversification potential. To provide the broadest possible indication of relative costs and profitability of different enterprises, several production levels are considered for each commodity including low, medium, and high-input management. The analysis suggests that chilli, potatoes, nilam, and oranges offer a potential for similar (or better) net profits and rates of return than tobacco. However, the markets for these alternative enterprises are generally far more limited than those for tobacco, and considerable investments may be needed to help smallholders to succeed with these crops, such as the development specialized support services and the expansion of private trading networks. Especially in the case of perennial crops with a long maturity period, a shift away from tobacco can be difficult or risk because of less certain cost structures, unknown market outlets, high establishment costs, and limited availability of seasonal and long-term credit. Considerable efforts will be required to overcome these and other practical barriers for tobacco farmers to take advantage of the diversification opportunities this report suggests are available.